1993
DOI: 10.1038/365454a0
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle myosin light chains are essential for physiological speeds of shortening

Abstract: In muscle each myosin head contains a regulatory light chain (LC2) that is wrapped around the head/rod junction, and an alkali light chain that is distal to LC2 (ref. 1). The role of these light chains in vertebrate skeletal muscle myosin has remained obscure. Here we prepare heavy chains that are free of both light chains in order to determine by a motility assay whether the light chains are necessary for movement. We find that removal of light chains from myosin reduces the velocity of actin filaments from 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
210
2
3

Year Published

1998
1998
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(234 citation statements)
references
References 18 publications
19
210
2
3
Order By: Relevance
“…A variety of mutational and light chain dissociation studies have suggested that an increase in the compliance of the lever arm yields a decrease in actin filament velocity (34,39,40). The slower contractile velocity of vertebrate smooth muscle relative to skeletal muscle (41) is probably due to numerous factors.…”
Section: Resultsmentioning
confidence: 99%
“…A variety of mutational and light chain dissociation studies have suggested that an increase in the compliance of the lever arm yields a decrease in actin filament velocity (34,39,40). The slower contractile velocity of vertebrate smooth muscle relative to skeletal muscle (41) is probably due to numerous factors.…”
Section: Resultsmentioning
confidence: 99%
“…Removing MLCs from chicken skeletal muscle myosin reduces the velocity of actin filament movement by 90% in an in vitro motility assay (21). Furthermore, MLC2 removal has little effect on isometric force, whereas MLC1 removal reduces the isometric force by over 50% (22).…”
Section: Discussionmentioning
confidence: 99%
“…The ELC of vertebrate striated muscle exist in two isoforms: alkali 1 (A1)-like and alkali 2 (A2)-like (6,7), and the presence of one, or the other, isoform appears to fine tune the contractile properties of the myosin molecule carrying it. This effect has been demonstrated in single muscle fibers (8), in in vitro motility assays (9), and in enzyme assays (10), where experiments are generally carried out with the more biochemically amenable myosin subfragment 1 (S1, a soluble, proteolytic fragment of myosin that retains the actin binding and MgATPase activities of the intact molecule). S1 prepared by chymotryptic digestion carries only one ELC and a fragment of the heavy chain (10).…”
mentioning
confidence: 99%